Effect of Water-Cement Ratio on Compressive Strength of Concrete with Granite Stone-Dust and Scoria. - Mukisa, Nathan (Kabale University, 2024)
There is always a need to test concrete for several properties before it is used at a construction site. This process is not only time-consuming but also takes additional resources in terms of labor and materials. This research was conducted to determine the standard mix design ratio for concrete with scoria aggregates for class C25/20. Stone dust (granite) was used as fine aggregates and ordinary Portland cement (CEMI 42.5N) was used as a binder. The research was initiated with the collection of materials like scoria aggregates from Kisoro, and granite stone dust from Kiyoora. Both scoria and granite were tested for a number of physical properties which aided in the determination of a trial mix design. The concrete which was prepared was tested for fresh and hardened properties. The results for compressive strength of cubes (150x150x150mm) were obtained after 3, 7, 14, and 28 days of curing. The optimum water-cement ratio for class C25/20 was found to be 0.52 depending on the average compressive strength of 26.3Mpa after 28 days of curing.